2001
DOI: 10.24033/bsmf.2388
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on Yu’s ‘property A’ for discrete metric spaces and groups

Abstract: Abstract. -Guoliang Yu has introduced a property on discrete metric spaces and groups, which is a weak form of amenability and which has important applications to the Novikov conjecture and the coarse Baum-Connes conjecture. The aim of the present paper is to prove that property in particular examples, like spaces with subexponential growth, amalgamated free products of discrete groups having property A and HNN extensions of discrete groups having property A. Résumé (Remarques sur la propriété A de Yu pour les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 12 publications
(13 reference statements)
1
77
0
Order By: Relevance
“…Tu proved, [15], that the fundamental group of a finite graph of groups in which each vertex group has property A will have property A. In [1], the author generalized Tu's results to groups acting by isometries on metric spaces with finite asdim .…”
Section: Asymptotic Dimension and Property Amentioning
confidence: 99%
See 1 more Smart Citation
“…Tu proved, [15], that the fundamental group of a finite graph of groups in which each vertex group has property A will have property A. In [1], the author generalized Tu's results to groups acting by isometries on metric spaces with finite asdim .…”
Section: Asymptotic Dimension and Property Amentioning
confidence: 99%
“…Higson and Roe [12] showed that finitely generated groups with finite asymptotic dimension have property A. In [15], J.-L. Tu proved that property A is preserved by the fundamental group of a finite graph of groups where the vertex groups all have property A. At first it was not known whether there could be a finitely generated group not having property A.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the corresponding result for free products with amalgam is considerably more difficult, in view of the fact that the common subgroup of the amalgam can introduce considerable distortion into the product. Our proof is based on a suitable adaptation of an argument given by Tu in his work on Property A [19]; although we are not able to verify a number of assertions concerning the metric defined in Section 9 in Tu's paper, we are able to adapt his arguments to the present context. The proof we give works equally well for countable exact groups (see Proposition 6.8 and Theorem 6.9), and is unrelated to Dykema's original proof that the class of countable exact groups is closed under free products with amalgam [9], [8].…”
Section: Theorem the Class Of Countable Discrete Groups That Are Unimentioning
confidence: 99%
“…Nevertheless, for our X Γ these inclusions are isometries, a fact that may be traced back to the manner in which the vertex and edge spaces of X Γ are metrized as subspaces of Γ, which circumvents any distortion that may have otherwise been introduced by the amalgamating subgroup. The following proposition has no analog in Tu's work [19]; nevertheless, we require it in order to complete our arguments.…”
Section: Ii) Every Vertex Space Of X γ Is Isometric To One Of a Or B mentioning
confidence: 99%
See 1 more Smart Citation